Hal-Hal yang Mendasari Penerapan Kurikulum 2013 - Anwar, Rusliansyah (Humaniora, 2014)
Eventhough there were pros and cons about a new curriculum, in the early academic year of 2013-2014 the Ministry of Education and Culture made an arrangement of new curriculum 2013. The curriculum would be done in classification (step by step) for basic education (elementary and secondary school) and also middle education. This study aims to get some information about the reason of the curriculum was designed. Moreover research used literature study to learn and understand the reason about government?s decision to implement the curriculum. The results showed that the curriculum is essentially an effort to simplify the curriculum using thematic-integrative model and emphasizing on natural, social, art, and culture phenomena. The emphasis is to enhance the ability of learners (students) to observe, ask, use their reason and communicate (present) their knowledge after receiving learning materials at school. Nonetheless, there are some things that should have serious attention from the government, which, if they are not anticipated, become obstacles to the successful implementation of the curriculum 2013. These things include training of the teachers and other education personnels to implement the curriculum 2013, the availability of handbook for teachers and students, as well as the governance readiness in education unit-level.